VD_FINDINFO Décision / 2013 / 101 vom 28. Dezember 2012 - VD Tribunal cantonal (2012)
AVOCAT D'OFFICE, CIRCULATION ROUTIÈREDROIT DE LA CIRCULATION ROUTIÈRE | 95 ch. 2 LCR, 96 ch. 1 LCR, 96 ch. 2 LCR, 132 CPP (CH)